Analisis Kapasitas Terminal Penumpang Di Bandar Udara SMB II Palembang - Lita Yarlina (Research and Development Agency of The Ministry of Transportation, 2012)
International airport is Sultan Mahmud Badaruddin II - Palembang included in the category of international bandra secondary collection services as the number of users between 1-5 million people per year, has served 2.1 million passenger movements both domestically and internationally, while the existing terminal with a 23,000 m2 was prepared just to serve 1 million passenger movements per year, the Sultan Mahmud airport terminal condition Badaruddin II Palembang now fairly solid enough. The condition of Sultan Mahmud International Airport Badaruddin II - Palembang is now a airport passenger terminal has the capacity to category 'medium 'which for some major facilities for the public service has met the technical requirements of the operation. Development is needed only at the departure hall and the vast number of seats for the passengers in the departure terminal which must be added the amount. The results of forecasting the number of passengers using linear regression and time series data of the total number of annual passengers arrive and depart at the airport Sultan Mahmud Badaruddin II - Palembang showed a linear trend increase is not so striking, the average increase per year increased only 174.631 people.Bandar udara internasional Sultan Mahmud Badaruddin II – Palembang termasuk dalam katagori bandara internasional pengumpul sekunder karena jumlah pengguna jasanya antara 1-5 juta orang per tahun, telah melayani 2,1 juta pergerakan penumpang baik domestic maupun internasional, sementara terminal yang ada saat ini dengan luas 23.000 m2 disiapkan hanya untuk melayani 1 juta pergerakan penumpang per tahun, maka kondisi terminal bandara Sultan Mahmud Badaruddin II Palembang saat ini terbilang sudah cukup padat. kondisi Bandara Internasional Sultan Mahmud Badaruddin II – Palembang saat ini merupakan bandar udara yang memiliki kapasitas terminal penumpang dengan katagori „menengah‟. Pengembangan yang dibutuhkan hanya pada luas hall keberangkatan dan jumlah tempat duduk untuk penumpang di terminal keberangkatan yang harus ditambah jumlahnya. Hasil peramalan jumlah penumpang dengan menggunakan regresi linier dan data time series dari jumlah total tahunan penumpang yang datang dan berangkat di Bandara Sultan Mahmud Badaruddin II – Palembang menunjukkan trend linier yang peningkatannya rata- per tahunnya hanya bertambah 174,631 orang.